Tire

CN122956883APending Publication Date: 2026-10-23SUMITOMO RUBBER INDUSTRIES LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202511955204.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-18
Filing Date
2025-12-23
Publication Date
2026-10-23

AI Technical Summary

Benefits of technology

[0019]根据本发明,可以实现轮胎的燃耗性能、湿抓地性能、耐磨耗性能的综合性能的进一步提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application aims to further improve the comprehensive performance of fuel consumption performance, wet grip performance, and wear resistance of a tire. A tire is provided with a tread portion formed using a rubber composition having a glass transition temperature Tg (°C) of -50°C or higher and -15°C or lower, the rubber composition containing, in 100 parts by mass of a rubber component, a styrene butadiene rubber (SBR) having a styrene content of less than 25% by mass, and, relative to 100 parts by mass of the rubber component, greater than 90 parts by mass of silica and greater than 55 parts by mass of a resin component, the glass transition temperature Tg (°C) and the thickness G (mm) of the tread portion satisfying the following formula. Tg × G < -150.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a tire. Background Technology

[0002] In recent years, various solutions have been proposed to meet the requirements for improving the fuel efficiency, grip, and wear resistance of tires installed on vehicles (for example, patent documents 1-4), but there is still a desire to further improve performance.

[0003] [Existing Technical Documents]

[0004] [Patent Literature]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 2019-218481

[0006] [Patent Document 2] Japanese Patent Application Publication No. 2020-59769

[0007] [Patent Document 3] Japanese Patent Application Publication No. 2021-25006

[0008] [Patent Document 4] Japanese Patent Application Publication No. 2022-121896 Summary of the Invention

[0009] [The problem the invention aims to solve]

[0010] The objective of this invention is to further improve the overall performance of tires in terms of fuel efficiency, wet grip, and wear resistance.

[0011] [Methods used to solve problems]

[0012] This invention relates to a tire.

[0013] It is a tire with a tread section, characterized in that,

[0014] The tread portion is formed using a rubber composition with a glass transition temperature (Tg) of -50°C to -15°C.

[0015] The rubber composition contains less than 25% by weight of styrene-butadiene rubber (SBR) in 100 parts by weight of the rubber component, and contains more than 90 parts by weight of silica and more than 55 parts by weight of resin component relative to 100 parts by weight of the rubber component.

[0016] The glass transition temperature Tg (°C) and the tread thickness G (mm) satisfy the following formula:

[0017] Tg×G<-150.

[0018] [The effects of the invention]

[0019] According to the present invention, the overall performance of tires, including fuel efficiency, wet grip, and wear resistance, can be further improved. Detailed Implementation

[0020] [1] Features of the tire of the present invention

[0021] First, the features of the tire of the present invention will be described.

[0022] 1. Summary

[0023] The tire of the present invention is a tire having a tread. The tread is formed using a rubber composition with a glass transition temperature Tg (°C) of -50°C to -15°C. In this rubber composition, 100 parts by mass of the rubber component contains less than 25% by mass of styrene-butadiene rubber (SBR), and, relative to 100 parts by mass of the rubber component, contains more than 90 parts by mass of silica and more than 55 parts by mass of resin. Furthermore, the product of the glass transition temperature Tg (°C) and the tread thickness G (mm) (Tg×G) is less than -150.

[0024] By possessing these characteristics, as described below, it is believed that the overall performance of tires, including fuel efficiency, wet grip, and abrasion resistance, can be further improved.

[0025] 2. The mechanism of the tire's performance effect according to the present invention

[0026] The mechanism by which the tire of the present invention exhibits the above-mentioned effects is believed to be as follows.

[0027] (1) Contains low-styrene SBR

[0028] As described above, the tread portion of the tire of the present invention contains styrene-butadiene rubber (SBR) with a styrene content of less than 25% by mass as a rubber component.

[0029] By using SBR with a low styrene content, specifically less than 25% by mass, tiny styrene domains can be formed within the rubber matrix. The formation of these small styrene domains then improves the tread's ability to rub against the road surface. Furthermore, the formation of these small styrene domains enhances the polymer's mobility, allowing it to move more flexibly. As a result, the polymer chains can more easily follow the road surface, leading to improved wet grip performance.

[0030] In the above, "styrene-butadiene rubber (SBR) containing less than 25% by mass of styrene as a rubber component" means that the total amount of styrene in the SBR is less than 25% by mass.

[0031] That is, when the rubber component contains one styrene-containing polymer (SBR), it means that the styrene content is less than 25% by mass. When the rubber component contains multiple styrene-containing polymers (SBR), it means that the styrene content is less than 25% by mass, calculated by the sum of the products of the styrene content (by mass%) of each polymer and the amount of that polymer mixed relative to 100 parts by mass of the rubber component.

[0032] More specifically, it means that when 100 parts by mass of rubber contain S1% by mass of SBR1 (X1 parts by mass) and S2% by mass of SBR2 (X2 parts by mass), the amount of styrene calculated by the formula {(S1×X1)+(S2×X2)} / (X1+X2) is less than 25% by mass.

[0033] In addition, the amount of styrene contained in the rubber component of the vulcanized rubber composition can be determined and calculated by solid-state nuclear magnetic resonance (solid-state NMR) or Fourier transform infrared spectrophotometer (FTIR).

[0034] (2) Contains silicon dioxide

[0035] As described above, the tread portion of the tire of the present invention further contains, as a reinforcing filler, a large amount of silica greater than 90 parts by mass relative to 100 parts by mass of the rubber component. By containing such a large amount of silica, not only is the heat generated by friction between silica particles increased, but friction between the flexible, small styrene regions and the silica also becomes easier to occur, thereby increasing the heat generation. Therefore, the tanδ at 30°C, described later, increases, which in turn increases energy loss. Furthermore, it can be considered that by containing a large amount of silica as a reinforcing filler, the reinforcement of the tread portion can be improved. As a result, improvements in tire fuel efficiency, wet grip, and abrasion resistance can be achieved.

[0036] (3) Contains resin components

[0037] As described above, the tread of the tire of the present invention contains, in addition to silica, a large amount of resin component in the form of more than 55 parts by mass relative to 100 parts by mass of rubber component. By containing such a large amount of resin component, the energy loss described above can be further increased. Furthermore, since the resin and polymer are more compatible, the polymer's flow properties and the dispersibility of silica can be further improved. As a result, improvements in tire fuel efficiency, wet grip, and abrasion resistance can be achieved.

[0038] (4) Glass transition temperature

[0039] As described above, the glass transition temperature (Tg) of the rubber composition constituting the tread of the tire of the present invention is above -50°C and below -15°C. By having such a low glass transition temperature, the tread can easily store heat in the low-temperature region. Furthermore, by allowing the rubber to remain soft even at low temperatures, it can better follow the road surface. As a result, improvements in tire fuel efficiency, wet grip, and abrasion resistance can be achieved.

[0040] The glass transition temperature of the aforementioned rubber composition can be determined by measuring the temperature distribution curve of the loss tangent (tanδ) using a viscoelasticity measuring device such as the "EPLEXOR" series manufactured by GABO. Specifically, the temperature distribution curve of tanδ is measured under the conditions of a frequency of 10 Hz, an initial strain of 10%, an amplitude of ±0.5%, and a heating rate of 2 °C / min. The temperature corresponding to the largest tanδ value in the range of -60 °C to 40 °C is taken as the glass transition temperature.

[0041] It should be noted that when there are two or more points with the largest tanδ value in the range above -60℃ and below 40℃, the point with the lowest temperature is taken as the glass transition temperature. For example, if a peak value of tanδ exists in the range above -60℃ and below 40℃, according to the above definition, the temperature of that peak value is taken as the glass transition temperature. Furthermore, for example, if a temperature distribution curve shows that the peak value of tanδ exists in the range below -60℃, and tanδ gradually decreases with increasing temperature in the range above -60℃ and below 40℃, then according to the above definition, the glass transition temperature is -60℃.

[0042] (5) Relationship between glass transition temperature and tread thickness

[0043] Furthermore, as described above, the product of the glass transition temperature Tg (°C) and the tread thickness G (mm) in the tire of the present invention (Tg×G) is less than -150. That is, it can be considered that by increasing the energy loss at the low temperature end and thickening the tread, energy loss is more likely to occur, especially when Tg is around -15 to -50°C. Moreover, since the tread can store heat more easily, the tire's fuel efficiency, wet grip, and wear resistance can be further improved.

[0044] In this invention, it can be considered that by synergistically leveraging the above-mentioned effects, not only is the mobility and reinforcement of the polymer improved, but energy loss can also be continuously generated even under repeated start / stop conditions, thereby achieving a further improvement in the overall performance of the tire in terms of fuel consumption, wet grip, and wear resistance.

[0045] [2] A more preferred embodiment of the tire of the present invention

[0046] The tire of the present invention can achieve more significant results by employing the following methods.

[0047] 1. Low-styrene SBR

[0048] As described above, in this invention, the tread portion contains low-styrene SBR with a styrene content of less than 25% by mass. In this case, it can be considered that as the styrene content decreases, the polymer's mobility increases, allowing for more flexible movement. The polymer chains become more easily responsive to the road surface, thereby further improving wet grip performance and achieving further improvements in tire fuel efficiency and abrasion resistance.

[0049] Specifically, the styrene content of the low-styrene SBR is more preferably 20% by mass or less, more preferably 15% by mass or less, and particularly preferably 10% by mass or less. On the other hand, as a lower limit, it is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 7% by mass or more.

[0050] It should be noted that the SBR content in 100 parts by weight of the rubber component is preferably 50 parts by weight or more, more preferably greater than 60 parts by weight, and even more preferably 70 parts by weight or more. As an upper limit, for example, it is preferably 90 parts by weight or less, more preferably 85 parts by weight or less, and even more preferably 80 parts by weight or less.

[0051] Furthermore, the glass transition temperature of the low-styrene SBR is preferably -25°C or lower, more preferably -40°C or lower, even more preferably -55°C or lower, and particularly preferably -70°C or lower. On the other hand, as a lower limit, it is preferably -95°C or higher, more preferably -90°C or higher, even more preferably -85°C or higher, and particularly preferably -80°C or higher.

[0052] 2.Tg×G

[0053] As described above, in this invention, the product of the glass transition temperature Tg (°C) and the thickness G (mm) of the tread (Tg×G) is less than -150, more preferably less than -180, and even more preferably less than -200.

[0054] 3. Silicon dioxide

[0055] As described above, in this invention, relative to 100 parts by weight of the rubber component, the content of silica is greater than 90 parts by weight, more preferably greater than 120 parts by weight, further preferably greater than 130 parts by weight, and particularly preferably greater than 140 parts by weight. On the other hand, there is no particular limitation on the upper limit, but it is preferably less than 190 parts by weight, more preferably less than 180 parts by weight, further preferably less than 170 parts by weight, and particularly preferably less than 160 parts by weight.

[0056] 4. Resin composition

[0057] As described above, in this invention, the content of the resin component is greater than 55 parts by weight, more preferably greater than 60 parts by weight, relative to 100 parts by weight of the rubber component. There is no particular upper limit, but it is preferably less than 75 parts by weight, more preferably less than 70 parts by weight.

[0058] Specific resin components include, for example, rosin-based resins, styrene-based resins, coumarone-based resins, terpene-based resins, C5 resins, C9 resins, C5C9 resins, and acrylic resins. Among these, C5 resins and C9 resins are more preferred, and dicyclopentadiene resins (DCPD resins) or AMS resins (α-methylstyrene resins) are particularly preferred. It should be noted that these resins can be hydrogenated resins.

[0059] 5. Glass transition temperature

[0060] As described above, in this invention, the glass transition temperature (Tg) of the rubber composition constituting the tread portion is -50°C or higher, -15°C or lower, more preferably -20°C or lower, and even more preferably -25°C or lower. On the other hand, as a lower limit, it is more preferably -40°C or higher, and even more preferably -30°C or higher.

[0061] 6. Relationship between SBR quantity and flatness ratio

[0062] Aspect ratio is the ratio of tire section height to tire section width. A higher aspect ratio (higher aspect ratio) means a smaller contact area with the road surface, resulting in improved overall wear resistance and anti-scratching performance. Conversely, as mentioned above, using SBR with low styrene content can also further improve overall wear resistance and anti-scratching performance.

[0063] Therefore, it can be considered that increasing the SBR content C in 100 parts by mass of the rubber component can improve the rubber composition. S The product of (parts by mass) and tire aspect ratio A (%) (C) S (×A), which can further improve the overall performance of wear resistance and spalling resistance.

[0064] Specifically, C S ×A is preferably greater than 2000, more preferably greater than 2500, and even more preferably greater than 3000. As an upper limit, there is no particular limitation; for example, it is preferably less than 4500, more preferably less than 4000, and even more preferably less than 3500.

[0065] 7. Relationship between silica content and negative profile ratio

[0066] Negative profile ratio refers to the ratio (%) of the total open area of ​​multiple grooves to the virtual contact area of ​​the tread surface when all multiple grooves are filled (the total contact area of ​​the tire's entire circumference when the tire with all multiple grooves filled is pressed against a flat surface under normal conditions of normal internal pressure and normal load). It can be considered that the smaller this ratio (low negative profile ratio), the larger the contact area with the road surface becomes, thus generating a large energy loss over the entire tread surface, thereby further improving wet grip performance.

[0067] On the other hand, it can be argued that by including a large amount of silica as a reinforcing filler, as described above, the overall performance of the tire, including fuel efficiency, wet grip, and wear resistance, can be further improved.

[0068] That is, it can be considered that by appropriately controlling the silica content C relative to 100 parts by mass of rubber component, SI Balancing the tire's (parts by weight) and negative profile ratio N (%) can further improve the overall performance of the tire, including fuel economy, wet grip, and wear resistance. Specifically, the ratio (C... SI The ratio ( / N) is preferably greater than 3, more preferably greater than 3.5. There is no particular upper limit, but for example, it is preferably less than 4.5, more preferably less than 4.

[0069] It should be noted that the above negative profile ratio can be obtained from the grounding shape under normal rim, normal internal pressure, and normal load conditions.

[0070] Specifically, the ground contact shape is obtained by assembling a tire onto a standard rim, applying standard internal pressure, allowing it to stand at 25°C for 24 hours, then applying ink to the tire surface, pressing it onto thick paper (camber angle 0°) under standard load, and transferring the image onto the thick paper. The tire is rotated 72° circumferentially each time, and the image is transferred at 5 positions. That is, 5 ground contact shapes are obtained. For the 5 ground contact shapes, the average of the maximum length along the tire axial direction is L, and the average of the length perpendicular to the axial direction is W. The negative profile ratio (%) is calculated as [1 - {average area of ​​the 5 ground contact shapes (ink portion) transferred to the thick paper / (L × W)}] × 100 (%). Here, the average length and area are a simple average of the 5 values, where L × W refers to the area of ​​the virtual surface obtained by connecting the blank portions corresponding to the main groove and transverse groove when obtaining the ground contact shape.

[0071] Here, "normal condition" means that the tire is assembled on a normal rim and filled with normal internal pressure, and is unloaded.

[0072] It should be noted that "standard rim" refers to the rim specified for each tire within a specification system that includes the tire's base specifications. For example, in JATMA (Japan Automobile Tire Association), it refers to the standard rim with applicable dimensions listed in the "JATMA Yearbook"; in ETRTO (European Tyre and Rim Technical Organization), it refers to the "Measuring Rim" listed in the "Standards Manual"; and in TRA (Tire and Rim Association, Inc.), it refers to the "Design Rim" listed in the "Yearbook". Refer to JATMA, ETRTO, and TRA in that order. If applicable dimensions are available when referring to these specifications, then follow those dimensions. Furthermore, in the case of tires not specified in the specifications, it refers to the rim with the smallest diameter and the narrowest width among rims that can be assembled with rims and can maintain internal pressure, that is, rims that will not leak air from between the rim and the tire.

[0073] Secondly, "standard tire pressure" refers to the air pressure specified for each tire within the specification system that includes the tire's underlying specifications. In JATMA, it refers to the "maximum air pressure," in ETRTO it refers to the "inflation pressure," and in TRA it refers to the maximum value recorded in the table "Tire Load Limits at Various Cold Inflation Pressures." Similar to standard rims, it is referenced in the order of JATMA, ETRTO, and TRA, and if an applicable size is available, that specification is used. Furthermore, in the case of tires not specified in the specifications, it refers to the standard tire pressure (of which, 250 kPa or higher) for other tire sizes (tire sizes specified in the specifications) recorded with the aforementioned standard rim as the standard rim. It should be noted that if multiple standard tire pressures of 250 kPa or higher are listed, the minimum value is used.

[0074] Additionally, "normal load" refers to the load specified for each tire within the specification system that includes the tire's base specification; it is the maximum mass allowed to be loaded onto the tire. In JATMA, it is "maximum load capacity"; in ETRTO specifications, it is "load capacity"; and in TRA, it refers to the maximum value recorded in the table "Tire load limits at various cold inflation pressures." Similar to "normal rim pressure" and "normal internal pressure," it is referenced in the order of JATMA, ETRTO, and TRA, and if applicable dimensions are available at the time of reference, that specification is followed. Next, in the case of tires not specified in the specifications, the normal load W is calculated using the following methods. L .

[0075] V = {(Dt / 2)} 2 -(Dt / 2-Ht) 2}×π×Wt

[0076] W L =0.000011×V+175

[0077] W L Normal load (kg)

[0078] V: Virtual volume of the tire (mm) 3 )

[0079] Dt: Tire outer diameter Dt (mm)

[0080] Ht: Tire section height (mm)

[0081] Wt: Tire cross-sectional width (mm)

[0082] 8. Relationship between resin composition and negative profile ratio

[0083] As mentioned above, it can be considered that by appropriately controlling the amount of resin component C relative to 100 parts by mass of rubber component, R Balancing the resin content (parts by weight) and the tire's negative profile ratio N (%) can improve wet grip performance. Specifically, the resin content C R The ratio of (parts by mass) to negative profile rate N (%) (C) R The ratio ( / N) is preferably greater than 1.5, more preferably greater than 1.7, and even more preferably greater than 2.0. As an upper limit, there is no particular limitation; for example, it is preferably less than 2.7, more preferably less than 2.5, and even more preferably less than 2.3.

[0084] 9. Particle size of silica

[0085] Considering the ease with which friction occurs with the polymer, the particle size (average primary particle size) of silica is preferably 16 nm or less. As a lower limit, it is preferably greater than 8 nm. It can be considered that by using silica with a small particle size, the contact frequency with the polymer (styrene region) can be increased, thereby improving wet grip performance during high-speed driving.

[0086] It should be noted that the average primary particle size is calculated by directly observing the silica extracted from the rubber composition cut from the tire using an electron microscope (TEM) or similar method, and by calculating the equivalent cross-sectional diameter based on the area of ​​each silica particle.

[0087] 10. Thickness and multi-layering of the tread area

[0088] The thickness of the tread portion is preferably 5 mm or more, more preferably 6 mm or more, and even more preferably 8 mm or more. Regarding the upper limit, it is preferably 20 mm or less, more preferably 18 mm or less, and even more preferably 16 mm or less. Therefore, it can be considered that the tread portion becomes more easily deformed by flexing, improving ground contact and thus enhancing wet grip performance.

[0089] Furthermore, the tread layer can be formed by a single layer, or by forming two layers with a base rubber layer inside the outermost tread rubber layer; alternatively, it can have three or four or more layers. In this case, the thickness of the tread rubber layer in the entire tread layer is preferably 10% or more. This allows sufficient friction to be generated between the tread surface and the road surface, enabling the transmission of sufficient frictional force to the tire interior, thereby further improving wet grip performance. It should be noted that, considering the friction generated between the tread surface and the road surface, the thickness of the tread rubber layer is more preferably 70% or more.

[0090] The tread rubber layer is not limited to the outermost tread rubber layer formed on the tread surface. If there are two or more layers within 5 mm from the tread surface inward, it is acceptable as long as at least one layer meets the conditions of the rubber composition.

[0091] It should be noted that the tread portion refers to the area that forms the contact patch with the tire, and it is the part located further outward in the radial direction from components containing fibrous materials, such as the carcass, belt ply, and belt reinforcement ply. The thickness of the tread portion can be measured by aligning the bead portion with the standard rim width in a cross-section cut along the radial direction of the tire.

[0092] Furthermore, the tread thickness refers to the thickness of the tread on the equatorial plane of the tire in the radial direction section of the tire. When the tread is formed by a single rubber composition, it is the thickness of that rubber composition; when it is formed by a laminated structure of multiple rubber compositions, it is the total thickness of these layers.

[0093] For example, in the case of a groove on the tire equatorial surface, the thickness refers to the distance from the intersection of the straight line connecting the outermost endpoint of the tire in the radial direction with the tire equatorial surface to the innermost interface of the tread in the radial direction.

[0094] The thickness of the tread can be calculated by adding the thickness of the driving tread rubber layer (the sum of all layers if there are 2 or more layers) and the thickness of the base rubber layer (the sum of all layers if there are 2 or more layers).

[0095] 11.30℃tanδ

[0096] In this invention, the loss tangent (30°C tanδ) of the rubber composition constituting the tread, measured in tensile deformation mode under conditions of 30°C, 10Hz, 5% initial strain, and 1% dynamic strain, is preferably 0.20 or more, more preferably 0.21 or more, and even more preferably 0.22 or more. On the other hand, as an upper limit, it is preferably 0.26 or less, more preferably 0.25 or less, and even more preferably 0.24 or less.

[0097] The loss angle tangent tanδ can be considered as a viscoelastic parameter representing the energy absorption performance. Since a larger value means more energy absorption, it can increase energy loss. Therefore, by controlling it to be above 0.20, it can help improve wet grip performance, thereby further improving the tire's fuel efficiency, wet grip performance, and wear resistance.

[0098] It should be noted that the loss tangent (tanδ) can be measured using a viscoelasticity measuring device, such as the "EPLEXOR (registered trademark)" manufactured by GABO.

[0099] Secondly, in this invention, the loss tangent (tanδ) can be increased, for example, by increasing the amount of styrene in the polymer, increasing the content of the resin component, increasing the content of carbon black, etc., and can be decreased by decreasing the amount of styrene in the polymer, decreasing the content of the resin component, decreasing the content of carbon black, etc.

[0100] 12. (0℃tanδ / 0℃E) * )×10 3

[0101] In this invention, the rubber composition constituting the tread portion preferably has the following properties: loss tangent (0°C tanδ) measured in tensile deformation mode under conditions of 0°C, 10Hz, initial strain 5%, and dynamic strain 2.5%; and complex elastic modulus (0°C E) measured in elongation deformation mode under conditions of 0°C, 10Hz, initial strain 5%, and dynamic strain 2.5%. * It satisfies the following formula.

[0102] [(0℃tanδ / 0℃E)] * )×10 3 >67.0

[0103] The complex elastic modulus can be considered as a parameter representing the rigidity of a rubber composition. The smaller the value, the softer the rubber becomes, which can suppress the occurrence of slippage between the rubber and the road surface, thereby improving the wear resistance.

[0104] Therefore, while increasing tanδ at 0℃, E at 0℃ is decreased. * By controlling [(0℃tanδ / 0℃E)] * )×10 3 A value greater than 67.0 can further improve the tire's fuel efficiency, wet grip, and wear resistance. More preferably, it is greater than 68.0, and even more preferably, greater than 70.0. There is no specific upper limit, but it is preferably below 80.0.

[0105] It should be noted that the determination of complex elastic modulus and loss tangent can also be performed using, for example, a viscoelasticity measuring device such as the "EPLEXOR (registered trademark)" manufactured by GABO.

[0106] Secondly, similar to the case of loss tangent, the complex elastic modulus can be increased by increasing the amount of styrene in the polymer, increasing the content of resin components, increasing the content of carbon black, increasing the amount of silica, etc., and can be decreased by decreasing the amount of styrene in the polymer, decreasing the content of resin components, decreasing the content of carbon black, etc.

[0107] [3] Implementation

[0108] The present invention will now be described in detail based on its embodiments.

[0109] 1. Rubber composition

[0110] In the tire of the present invention, the rubber composition forming the tread (tread rubber composition) can be obtained by appropriately adjusting the types and quantities of various compounding materials such as the rubber components, fillers, softeners, vulcanizing agents and vulcanization accelerators described below.

[0111] (1) Compounding materials

[0112] (a) Rubber composition

[0113] As mentioned above, low-styrene SBR and isoprene-based rubbers were used as rubber components. Other rubber components that can be used include diene rubbers such as butadiene rubber (BR) and nitrile rubber (NBR), butyl rubbers such as butyl rubber, and thermoplastic elastomers such as styrene-butadiene-styrene block copolymer (SBS) and styrene-butadiene block copolymer (SB), which are commonly used in tire manufacturing.

[0114] (I) SBR

[0115] The weight-average molecular weight of the SBR is, for example, greater than 100,000 and less than 2,000,000. Secondly, in this invention, as described above, the styrene content in the SBR composition is less than 25% by mass. The vinyl content (1,2-bonded butadiene content) of the SBR is, for example, greater than 5% by mass and less than 70% by mass. It should be noted that the vinyl content of the SBR refers to the 1,2-bonded butadiene content relative to the total butadiene portion of the SBR composition. Furthermore, the structural identification of the SBR (determination of styrene content and vinyl content) can be performed, for example, by NMR determination. 1 H-NMR or 13 The analysis was performed using C-NMR. The content of components such as "styrene content" was compared with the complex elastic modulus (E). * Unlike physical properties, true values ​​exist that are independent of the measurement method; therefore, it is preferable to use the most accurate measurement method possible. It should be noted that the SBR content in 100 parts by mass of the rubber component is as described above.

[0116] There are no particular limitations on the type of SBR used; for example, emulsion-polymerized styrene-butadiene rubber (E-SBR) and solution-polymerized styrene-butadiene rubber (S-SBR) can be used. The SBR can be either unmodified or modified. Alternatively, hydrogenated SBR, obtained by hydrogenating the butadiene portion of the SBR, can also be used. Hydrogenated SBR can be obtained by subsequently hydrogenating the BR portion of the SBR, or by copolymerizing styrene, ethylene, and butadiene to achieve the same structure. It should be noted that the SBR content per 100 parts by weight of the rubber component is as described above.

[0117] As a modified SBR, any SBR having a functional group that interacts with fillers such as silica is acceptable. Examples include end-modified SBRs (end-modified SBRs with the aforementioned functional groups at the end) where at least one end of the SBR is modified with a compound (modifier) ​​having the aforementioned functional groups, main-chain modified SBRs with the aforementioned functional groups on the main chain, main-chain end-modified SBRs with the aforementioned functional groups on both the main chain and the end (e.g., main-chain end-modified SBRs with the aforementioned functional groups on the main chain and at least one end modified by the aforementioned modifier), and end-modified SBRs that introduce hydroxyl or epoxy groups by modification (coupling) with a polyfunctional compound having two or more epoxy groups in the molecule.

[0118] Examples of the aforementioned functional groups include, for example, amino, amide, silyl, alkoxysilyl, isocyanate, imino, imidazo, urea, ether, carbonyl, oxycarbonyl, mercapto, thioether, dithioether, sulfonyl, sulfinyl, thiocarbonyl, ammonium, imide, hydrazine, azo, diazo, carboxyl, nitrile, pyridyl, alkoxy, hydroxyl, oxygen, and epoxy groups. It should be noted that these functional groups may have substituents.

[0119] Alternatively, as a modified SBR, for example, an SBR modified with a compound (modifier) ​​represented by the following formula can be used.

[0120]

Chemistry 1

[0121]

[0122] It should be noted that, in the formula, R 1 R 2 and R 3 They may be the same or different, representing alkyl, alkoxy, silyloxy, acetal, carboxyl (-COOH), mercapto (-SH), or derivatives thereof. R 4 and R 5 They can be the same or different, representing hydrogen atoms or alkyl groups. R 4 and R 5 It can bond and form a ring structure with nitrogen atoms. n represents an integer.

[0123] As a modified SBR modified by the compound (modifier) ​​represented by the above formula, an SBR obtained by modifying the polymerization end (active end) of solution-polymerized styrene-butadiene rubber (S-SBR) with the compound represented by the above formula can be used (modified SBR, etc. as described in Japanese Patent Application Publication No. 2010-111753).

[0124] As R 1 R 2 and R 3Preferably, it is an alkoxy group (preferably an alkoxy group with 1 to 8 carbon atoms, more preferably an alkoxy group with 1 to 4 carbon atoms). As R 4 and R 5 Preferably, it is an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms). n is preferably 1 to 5, more preferably 2 to 4, and even more preferably 3. Additionally, R... 4 and R 5 When bonded together with nitrogen atoms to form a cyclic structure, a 4- to 8-membered ring is preferred. It should be noted that alkoxy groups also include cycloalkoxy groups (such as cyclohexyloxy groups) and aryloxy groups (such as phenoxy and benzyloxy groups).

[0125] Specific examples of the aforementioned modifiers include 2-dimethylaminoethyltrimethoxysilane, 3-dimethylaminopropyltrimethoxysilane, 2-dimethylaminoethyltriethoxysilane, 3-dimethylaminopropyltriethoxysilane, 2-diethylaminoethyltrimethoxysilane, 3-diethylaminopropyltrimethoxysilane, 2-diethylaminoethyltriethoxysilane, and 3-diethylaminopropyltriethoxysilane. These can be used individually or in combination of two or more.

[0126] Additionally, modified SBRs can also be made using compounds (modifiers) such as: polyethylene glycol diglycidyl ether, glycerol triglycidyl ether, trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, etc., polyglycidyl ethers of polyols; polyglycidyl ethers of aromatic compounds having two or more phenolic groups, such as diglycidylated bisphenol A; polyepoxide compounds such as 1,4-diglycidylbenzene, 1,3,5-triglycidylbenzene, and polyepoxide liquid polybutadiene; tertiary amines containing epoxy groups, such as 4,4'-diglycidyl diphenylmethylamine and 4,4'-diglycidyl dibenzylmethylamine; diglycidyl aniline, N,N'-diglycidyl-4-glycidyloxyaniline, and diglycidyl o-toluidine. Tetraglycidyl-m-phenylenediamine, tetraglycidylaminodiphenylmethane, tetraglycidyl-p-phenylenediamine, diglycidylaminomethylcyclohexane, tetraglycidyl-1,3-diaminomethylcyclohexane, and other diglycidylamino compounds; bis(1-methylpropyl)carbamoyl chloride, 4-morpholinocarbonyl chloride, 1-pyrrolidinecarbonyl chloride, N,N-dimethylformyl chloride, N,N-diethylformyl chloride, and other amino-containing acyl chlorides; 1,3-bis(glycidyloxypropyl)tetramethyldisiloxane, (3-glycidyloxypropyl)pentamethyldisiloxane, and other epoxy-containing silane compounds; (trimethylsilyl)[3-(trimethoxysilyl)propyl]sulfide, (trimethylsilyl)[ Silane compounds containing thioether groups, such as 3-(triethoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(tripropoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(tributoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(methyldimethoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(methyldiethoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(methyldipropoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(methyldibutoxysilyl)propyl] sulfide, etc.; N-substituted aziridine compounds such as ethyleneimine and acrylimine; methyltriethoxysilane, N,N-bis(trimethylsilyl)-3-amino Alkoxysilanes such as propyltrimethoxysilane, N,N-bis(trimethylsilyl)-3-aminopropyltriethoxysilane, N,N-bis(trimethylsilyl)aminoethyltrimethoxysilane, and N,N-bis(trimethylsilyl)aminoethyltriethoxysilane; (thio)benzophenone compounds having amino groups and / or substituted amino groups, such as 4-N,N-dimethylaminobenzophenone, 4-N,N-di-tert-butylaminobenzophenone, 4-N,N-diphenylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, and N,N,N',N'-bis(tetraethylamino)benzophenone.Benzaldehyde compounds containing amino groups and / or substituted amino groups, such as 4-N,N-dimethylaminobenzaldehyde, 4-N,N-diphenylaminobenzaldehyde, and 4-N,N-divinylaminobenzaldehyde; N-substituted pyrrolidones such as N-methyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, N-phenyl-2-pyrrolidone, N-tert-butyl-2-pyrrolidone, and N-methyl-5-methyl-2-pyrrolidone; N-substituted piperidinones such as N-methyl-2-piperidinone, N-vinyl-2-piperidinone, and N-phenyl-2-piperidinone; N-methyl-ε-caprolactam, N-phenyl-ε-caprolactam, N-methyl-ω-laurolactam, N-vinyl-ω-laurolactam, N-methyl-β-propiolactam, and N- N-substituted lactams such as phenyl-β-propiolactam; and N,N-bis(2,3-epoxypropoxy)-aniline, 4,4-methylenebis(N,N-glycidylaniline), tris(2,3-epoxypropyl)-1,3,5-triazine-2,4,6-triones, N,N-diethylacetamide, N-methylmaleimide, N,N-diethylurea, 1,3-dimethylvinylurea, 1,3-divinylvinylurea, 1,3-diethyl-2-imidazolinone, 1-methyl-3-ethyl-2-imidazolinone, 4-N,N-dimethylaminoacetophenone, 4-N,N-diethylaminoacetophenone, 1,3-bis(diphenylamino)-2-propanone, 1,7-bis(methylethylamino)-4-heptanone, etc. It should be noted that modification using the above compounds (modifiers) can be carried out by known methods.

[0127] As an SBR (Self-Borne Blender), for example, SBRs manufactured and sold by companies such as Sumitomo Chemical Co., Ltd., ENEOS Materials Co., Ltd., Asahi Kasei Corporation, and Zeon Corporation of Japan can be used. It should be noted that SBRs can be used alone or in combination of two or more types.

[0128] (II) Isoprene-based rubber

[0129] Examples of isoprene-based rubbers include natural rubber (NR), modified natural rubber (modified NR), modified natural rubber (modified NR), and synthetic polyisoprene (isoprene rubber (IR), modified isoprene rubber (modified IR)). Among these, NR, which exhibits superior strength, is preferred. It should be noted that the content of isoprene-based rubber in 100 parts by mass of the rubber component is preferably 5 parts by mass or more, more preferably 8 parts by mass or more. As an upper limit, for example, it is preferably 40 parts by mass or less, more preferably 20 parts by mass or less.

[0130] For specific types of natural rubber (NR), products commonly used in the tire industry, such as SVR-L, SIR20, RSS#3, and TSR20, can be used. For natural rubber (IR), there are no particular limitations, and products commonly used in the tire industry, such as IR2200, can be used. For modified NR, examples include deproteinized natural rubber (DPNR) and high-purity natural rubber (UPNR). For modified NR, examples include epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), and grafted natural rubber. For modified IR, examples include epoxidized isoprene rubber, hydrogenated isoprene rubber, and grafted isoprene rubber. These can be used individually or in combination of two or more types.

[0131] (III) BR

[0132] In this invention, BR may be further included as needed. In this case, the BR content in 100 parts by weight of the rubber component is preferably 5 parts by weight or more, more preferably 7 parts by weight or more, and even more preferably 10 parts by weight or more. On the other hand, it is preferably 45 parts by weight or less, more preferably 43 parts by weight or less, and even more preferably 40 parts by weight or less.

[0133] The weight-average molecular weight of BR is, for example, greater than 100,000 and less than 2,000,000. The vinyl content of BR is, for example, greater than 1% by mass and less than 30% by mass. The cis content of BR is, for example, greater than 1% by mass and less than 98% by mass. The trans content of BR is, for example, greater than 1% by mass and less than 60% by mass.

[0134] There are no particular limitations on the type of BR used; BR with high cis content (cis content above 90%), low cis content, and BR containing syndiotactic polybutadiene crystals can all be used. BR can be either unmodified or modified; examples of modified BR include those incorporating the aforementioned functional groups. These can be used individually or in combination of two or more. It should be noted that the cis content can be determined using infrared absorption spectroscopy.

[0135] As a BR (Brandinger), products from companies such as Ube Industries, Inc., ENEOS Materials Co., Ltd., Asahi Kasei Corporation, and Zeon Corporation can be used.

[0136] (IV) Other rubber components

[0137] In addition, as other rubber components, nitrile rubber (NBR) and other rubbers (polymers) commonly used in tire manufacturing may be included as needed.

[0138] The raw materials (monomers) for the aforementioned SBR, BR and other synthetic rubbers can be substances derived from petroleum or substances recycled from rubber products such as tires and non-rubber products such as polystyrene.

[0139] The monomer obtained through recycling (recycled monomer) is not particularly limited, and examples include recycled isoprene, recycled butadiene, and recycled aromatic vinyl compounds. Examples of butadiene include 1,2-butadiene and 1,3-butadiene. Examples of aromatic vinyl compounds are not particularly limited, and examples include styrene. Preferably, recycled butadiene and / or recycled styrene are used as raw materials.

[0140] There are no particular limitations on the manufacturing method of the recycled monomer. For example, it can be synthesized from recycled naphtha obtained by decomposing rubber products such as tires. Furthermore, there are no particular limitations on the manufacturing method of the recycled naphtha. For example, rubber products such as tires can be decomposed under high temperature and pressure, microwave decomposition can be used, or extraction can be performed after mechanical crushing.

[0141] Furthermore, the raw materials (monomers) for synthetic rubbers such as SBR and BR can be derived from biomass. There are no particular limitations on the types of monomers derived from biomass, and examples include butadiene and aromatic vinyl compounds derived from biomass. Examples of butadiene include 1,2-butadiene and 1,3-butadiene. Examples of aromatic vinyl compounds are not particularly limited, and examples include styrene. Additionally, there are no particular limitations on the methods for producing biomass monomers; for example, they can be obtained through biological and / or chemical and / or physical transformation of plants and animals. A representative example of biological transformation is microbial fermentation; examples of chemical and / or physical transformation include catalyst-based transformation, high-temperature-based transformation, high-pressure-based transformation, electromagnetic wave-based transformation, supercritical fluid-based transformation, and combinations thereof. Examples of biomass sources for these monomers include sugar and wood, plant residues after obtaining useful components, ethanol from plants, and biomass naphtha.

[0142] The term "biomass polymer" is not particularly limited to polymers synthesized from biomass monomer components. Examples include polybutadiene rubber synthesized from butadiene derived from biomass, and aromatic vinyl / butadiene copolymers synthesized from butadiene derived from biomass and / or aromatic ethylene derived from biomass. Examples of such aromatic vinyl / butadiene copolymers include, for instance, styrene-butadiene rubber synthesized from butadiene derived from biomass and / or styrene derived from biomass.

[0143] Whether the polymer's raw material comes from biomass can be determined by the pMC (percent Modern Carbon) measured based on ASTM D6866-10.

[0144] pMC refers to the sample 14 C concentration relative to standard modern carbon (modern standard reference) 14 The ratio of C concentration is an indicator used to represent the biomass ratio of the compound (rubber). The significance of this value is explained below.

[0145] 1 mole of carbon atoms (6.02 × 10⁻⁶) 23 Of these, approximately one trillionth, or about 6.02 × 10⁻⁶, is present. 11 Individual 14 C. 14 Carbon (C) is known as a radioactive isotope with a half-life of 5730 years, decreasing regularly. All of these decays take 226,000 years to completely decompose. Therefore, it can be considered that the carbon dioxide and other substances in the atmosphere, after being fixed by plants and taking more than 226,000 years to form fossil fuels such as coal, oil, and natural gas, initially fixed and contained within these fossil fuels, represent a significant portion of the carbon dioxide that was initially fixed within them. 14 Carbon has completely decayed. Therefore, in the 21st century, fossil fuels such as coal, oil, and natural gas contain absolutely no carbon. 14 Therefore, the chemicals produced from these fossil fuels contain absolutely no carbon (C). 14 C element.

[0146] On the other hand, cosmic rays undergo nuclear reactions in the atmosphere, continuously generating... 14 C, and the consequences of radioactive decay 14 The phase equilibrium of decreasing carbon, in Earth's atmospheric environment, 14 The amount of C is constant. Therefore, as mentioned above, the matter from biomass resources undergoing material cycling in the current environment... 14 The C concentration relative to all C atoms is approximately 1 × 10⁻⁶. -12 The values ​​are approximately mol%. Therefore, the difference between these values ​​can be used to calculate the proportion of compounds derived from natural resources (compounds derived from biomass) in a given compound (rubber) (biomass ratio).

[0147] Should 14 C is typically determined as follows. Accelerator mass spectrometry based on a tandem accelerator is used for the determination. 13 C concentration ( 13 C / 12 C) 14 C concentration ( 14 C / 12C) Determination. In the determination, as... 14 The standard for C concentration in modern carbon is based on the carbon in the natural cycle as of 1950. 14 C concentration. As a specific standard substance, the oxalic acid standard provided by NIST (National Institute of Standards and Technology) was used. The radioactivity of carbon in this oxalic acid (carbon content per gram of carbon) was determined. 14 The radioactivity intensity of C is differentiated by each carbon isotope. 13 The C-correction is a fixed value, and the decay-corrected value from 1950 to the date of measurement is used as the standard. 14 The value of C concentration (100%). The ratio of the actual measured value of the sample to this value is the pMC value.

[0148] Therefore, if rubber is made from materials derived from 100% biomass (natural sources), then despite regional differences, it will show a value of approximately 110 pMC (currently, under normal circumstances, it is mostly not 100). On the other hand, for chemicals derived from fossil fuels such as petroleum, when measuring... 14 At C concentration, it shows approximately 0 pMC (e.g., 0.3 pMC). This value corresponds to 0% of the biomass ratio described above.

[0149] In conclusion, using rubber or other materials with high pMC values, i.e., high biomass ratios, in rubber compositions is preferred from the perspective of being beneficial to environmental protection and enhancing sustainability.

[0150] (b) Compound materials other than rubber components

[0151] (I) Filler

[0152] As mentioned above, the rubber composition contains silica as a reinforcing filler, but in addition to silica, it may also contain carbon black, graphite, calcium carbonate, talc, alumina, clay, aluminum hydroxide, mica, etc.

[0153] (i-1)Silica

[0154] From the perspective of achieving good durability, the BET specific surface area of ​​silica is preferably greater than 140 m². 2 / g, more preferably greater than 160m 2 / g. On the other hand, from the viewpoint of obtaining good rolling resistance at high speeds, a value of less than 300m is preferred. 2 / g, more preferably less than 250m 2 / g, further preferably less than 220m 2 / g. It should be noted that the above BET specific surface area is the N2SA value determined by the BET method according to ASTM D3037-93.

[0155] At this point, the particle size (average primary particle size) of silica, as described above, is preferably 16 nm or less. It should be noted that the silica content relative to 100 parts by mass of the rubber component is as described above.

[0156] Specific examples of silica include dry-process silica (anhydrous silica) and wet-process silica (hydrated silica). Wet-process silica is preferred due to its higher silanol group content. Additionally, silica made from materials such as hydrous glass or biomass materials such as rice husks can also be used.

[0157] As silicon dioxide, products from companies such as Evonik Industries, Rhodia, Tosoh Silicon Chemicals, Solvay Japan, and Tokuyama Corporation can be used.

[0158] There are no particular limitations on the raw materials used for silica. For example, raw materials derived from minerals such as quartz, raw materials derived from organisms such as rice husks (e.g., silica made from biomass materials such as rice husks), and silica recovered from silica-containing products can also be used. Among these, hydrated silica prepared by a wet process is preferred due to the high prevalence of silanol groups.

[0159] As a biomass material, silica can be obtained by extracting silicates from rice husk ash obtained by burning rice husks using sodium hydroxide solution. The silicates are then reacted with sulfuric acid in the same way as existing wet silica. The resulting silica precipitate is then filtered, washed, dried, and pulverized.

[0160] Silica recovered from products containing silica can be, for example, silica recovered from products containing silica such as electronic components like semiconductors, tires, desiccants, and filter materials such as diatomaceous earth. Furthermore, the method of recovery is not particularly limited, and examples include thermal decomposition and electromagnetic wave decomposition. Of these, silica recovered from electronic components like semiconductors or tires is preferred.

[0161] If silica crystallizes, it becomes insoluble in water, making it impossible to utilize its silicic acid component. By managing the combustion temperature and time, the crystallization of silica in rice husk ash can be suppressed (see Japanese Patent Application Publication No. 2009-2594, Akita Prefectural University Online Journal B, 2019, vol.6, pp.216-222, etc.).

[0162] Amorphous silica extracted from rice husks can be commercially available from companies such as Wilmar.

[0163] It should be noted that these silicas can be used alone or in combination with two or more types. Furthermore, from the perspective of environmental protection and sustainability, the use of biomass silica and recycled silica is preferred.

[0164] (i-2) Silane coupling agent

[0165] When using the above-mentioned silica, it is preferable to include a silane coupling agent together with the silica.

[0166] As a silane coupling agent, there are no particular limitations; examples include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, and bis(4-trimethoxysilylbutyl)tetrasulfide. 3-Triethoxysilylpropyl disulfide, bis(3-triethoxysilylpropyl) disulfide, bis(2-triethoxysilylethyl) disulfide, bis(4-triethoxysilylbutyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, bis(2-trimethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyltetrasulfide The sulfide system includes compounds such as 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide and 3-triethoxysilylpropyl methacrylate monosulfide; mercapto-based systems such as 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and NXT and NXT-Z manufactured by Momentive; vinyl-based systems such as vinyltriethoxysilane and vinyltrimethoxysilane; amino-based systems such as 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; glycidoxy-based systems such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based systems such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; and chlorine-based systems such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane. Among these, mercapto-based silane coupling agents are preferred. They can be used individually or in combination of two or more.

[0167] As silane coupling agents, products from companies such as Evonik Industries, Momentive, Shin-Etsu Silicones, Tokyo Chemical Industries, Azmax, and DuPont Toray Specialty Materials can be used.

[0168] The content of silane coupling agent is, for example, greater than 3 parts by mass and less than 25 parts by mass relative to 100 parts by mass of silicon dioxide.

[0169] (II) Carbon black

[0170] From the viewpoint of improving wet grip by enhancing rigidity and responsiveness, carbon black is preferably included as a reinforcing filler in addition to silica.

[0171] The specific content of carbon black relative to 100 parts by mass of rubber component is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 4 parts by mass or more. On the other hand, it is preferably 30 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 12 parts by mass or less.

[0172] There are no particular limitations on carbon black. Examples include furnace black (furnace black) such as SAF, ISAF, HAF, MAF, FEF, SRF, GPF, APF, FF, CF, SCF, and ECF; acetylene black; thermal cracking black (thermal cracking black) such as FT and MT; and channel black (channel black) such as EPC, MPC, and CC. One of these can be used alone, or two or more can be used in combination.

[0173] The preferred CTAB specific surface area (Cetyl Tri-methyl Ammonium Bromide) of carbon black is 130 m². 2 / g or more, more preferably 160m 2 / g or more, further preferably 170m 2 / g or more. On the other hand, 250m is preferred. 2 / g or less, more preferably 200m 2 / g or less. It should be noted that the CTAB specific surface area is a value determined according to ASTM D3765-92.

[0174] There are no specific limitations on the specific type of carbon black used; examples include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. Commercially available products include those from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Co., Ltd., Lion Corporation, Shin Nippon Chemical Carbon Co., Ltd., and Columbia Carbon Co., Ltd. These can be used individually or in combination of two or more types.

[0175] (iii) Other fillers

[0176] In addition to silica and carbon black, the rubber composition may, as needed, contain fillers commonly used in the tire industry, such as graphite, calcium carbonate, talc, alumina, clay, aluminum hydroxide, and mica. The content of these fillers relative to 100 parts by weight of the rubber component is, for example, greater than 0.1 parts by weight and less than 200 parts by weight.

[0177] (II) Plasticizer components

[0178] To ensure proper dispersion of powdered materials during mixing, plasticizer components are preferably used in the rubber composition as needed. It should be noted that plasticizer components here refer to additives such as processing oils or rubber components, liquid rubber, and resin components, which plasticize the rubber composition.

[0179] These plasticizer components can be derived from petroleum, biomass, or naphtha recycled from rubber or non-rubber products. Alternatively, low-molecular-weight hydrocarbon components obtained through the thermal cracking and extraction of used tires or products containing various components can be used as plasticizers. Among these, plasticizer components derived from biomass or recycled materials are preferred as sustainable plasticizer components.

[0180] It should be noted that the aforementioned plasticizer components can be used alone or in combination with two or more. In this case, the content of the plasticizer component relative to 100 parts by weight of the rubber component is preferably 20 parts by weight or more, more preferably 30 parts by weight or more, and even more preferably 40 parts by weight or more. As an upper limit, for example, it is preferably 100 parts by weight or less, more preferably 80 parts by weight or less, and even more preferably 60 parts by weight or less.

[0181] It should be noted that the content of plasticizer components also includes the amount of oil contained in rubber (oil-extended rubber), etc.

[0182] (i) Oil

[0183] Examples of oils include, for example, mineral oils (usually referring to processing oils), vegetable oils, or mixtures thereof. Examples of mineral oils (processing oils) include paraffinic processing oils, aromatic processing oils, and cycloalkane processing oils. Examples of vegetable oils include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, rosin, pine oil, pine tar, tall oil, corn oil, rice bran oil, safflower oil, sesame oil, olive oil, sunflower seed oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, and tung oil. These can be used alone or in combination of two or more. Additionally, from a life cycle assessment perspective, waste oil or waste cooking oil used as lubricant in rubber mixing mills or automotive engines can also be appropriately utilized.

[0184] As specific processing oils (mineral oils), products from companies such as Idemitsu Kosan Co., Ltd., Sankyo Oil & Chemical Co., Ltd., ENEOS Co., Ltd., OLISOY Co., Ltd., H&R Co., Ltd., Toyokuni Oil Co., Ltd., Showa Shell Oil Co., Ltd., and Fuji Kosan Co., Ltd. can be used.

[0185] (ii) Liquid rubber

[0186] Liquid rubber, as an example of a plasticizer component, refers to polymers that are liquid at room temperature (25°C), and is a rubber component that can be extracted from vulcanized tires using acetone. Examples of liquid rubber include farnesene polymers, liquid diene polymers, and their hydrides.

[0187] Farnesene polymers refer to polymers obtained by polymerizing farnesenes and possessing structural units based on farnesenes. Farnesenes exist as isomers such as α-farnesene ((3E,7E)-3,7,11-trimethyl-1,3,6,10-dodecathetene) and β-farnesene (7,11-dimethyl-3-methylene-1,6,10-dodecathetene).

[0188] Farnesene polymers can be homopolymers of farnesene (farnesene homopolymers) or copolymers of farnesene and vinyl monomers (farnesene-vinyl monomer copolymers).

[0189] Examples of liquid diene polymers include liquid styrene-butadiene copolymer (liquid SBR), liquid butadiene polymer (liquid BR), liquid isoprene polymer (liquid IR), and liquid styrene-isoprene copolymer (liquid SIR).

[0190] The weight-average molecular weight (Mw) of polystyrene, determined by gel permeation chromatography (GPC) of liquid diene polymers, is, for example, greater than 1.0 × 10⁻⁶. 3 Less than 2.0×10 5 It should be noted that, in this specification, the Mw of the liquid diene polymer is a polystyrene conversion value determined by gel permeation chromatography (GPC).

[0191] The content of liquid rubber (the total content of liquid farnesene polymers, liquid diene polymers, etc.) is, for example, greater than 1 part by mass and less than 100 parts by mass relative to 100 parts by mass of rubber component.

[0192] As a liquid rubber, products from companies such as Kuraray Corporation and Clayville Corporation can be used.

[0193] (iii) Resin composition

[0194] The resin component also functions as an adhesive agent. It can be solid or liquid at room temperature. Specific resin components can be the resins mentioned above, or two or more can be used in combination. Furthermore, these resin components can be modified with groups that can react with silica, etc., as needed. It should be noted that the content of resin component relative to 100 parts by mass of rubber component is as described above.

[0195] Rosin-based resins are resins obtained by processing rosin, with rosin acid as the main component. These rosin-based resins (rosin derivatives) can be classified according to whether they have been modified or not, into unmodified rosin and modified rosin derivatives. Examples of unmodified rosin include tall oil rosin, resin rosin, wood rosin, disproportionated rosin, polymerized rosin, hydrogenated rosin, and rosin with other chemical modifications. Modified rosin derivatives are modifications of unmodified rosin, including rosin esters, unsaturated carboxylic acid-modified rosin derivatives, unsaturated carboxylic acid-modified rosin esters, rosin amide compounds, and rosin amine salts.

[0196] Styrene-based resins are polymers that use styrene-based monomers as constituent monomers. Examples include polymers polymerized with styrene-based monomers as the main component (50% by mass or more). Specifically, in addition to homopolymers obtained by homopolymerization of styrene-based monomers (styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-methoxystyrene, p-tert-butylstyrene, p-phenylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, etc.), copolymers obtained by copolymerization of two or more styrene-based monomers, copolymers of styrene-based monomers and other monomers that can be copolymerized with them can also be listed.

[0197] Other monomers mentioned above may include acrylonitrile, methacrylonitrile and other acrylonitrile derivatives; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated carboxylic acid esters such as methyl acrylate and methyl methacrylate; dienes such as chloroprene, butadiene, and isoprene; alkenes such as 1-butene and 1-pentene; and α,β-unsaturated carboxylic acids or their anhydrides such as maleic anhydride.

[0198] Among coumarone-based resins, coumarone-indene resin is preferred. Coumarin-indene resin is a resin containing coumarone and indene as monomeric components constituting the resin backbone (main chain). Other monomeric components in the backbone besides coumarone and indene include styrene, α-methylstyrene, methylindene, and vinyltoluene.

[0199] The content of coumarin indole resin relative to 100 parts by weight of rubber component is, for example, greater than 1.0 parts by weight and less than 50.0 parts by weight.

[0200] The hydroxyl value (OH value) of coumarin indole resin is, for example, greater than 15 mg KOH / g and less than 150 mg KOH / g. It should be noted that the OH value refers to the amount of potassium hydroxide, expressed in milligrams, required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of resin is acetylated; this value is determined by potentiometric titration (JIS K 0070:1992).

[0201] The softening point of coumarin indene resin is, for example, greater than 30°C and less than 160°C. Furthermore, the softening point is the temperature at which the ball drops when measured using a ring and ball softening point tester as specified in JIS K 6220-1:2001.

[0202] Examples of terpene-based resins include polyterpenes, terpene phenols, and aromatic modified terpene resins. Polyterpenes are resins obtained by polymerizing terpene compounds and their hydrides. Terpene compounds are composed of (C5H8) resins. n The composition of hydrocarbons and their oxygen-containing derivatives is represented by the composition of monoterpenes (C14-C24-C24). 10 H 16 ), sesquiterpenes (C 15 H 24 ), diterpenes (C 20 H 32 Compounds with terpenes as their basic skeleton, such as α-pinene, β-pinene, dipentene, limonene, myrcene, allocirrhene, ocimene, α-phellandrene, α-terpinene, γ-terpinene, terpinene oil, 1,8-cineole, 1,4-cineole, α-terpineol, β-terpineol, γ-terpineol, etc.

[0203] As polyterpenes, in addition to terpene resins such as α-pinene resin, β-pinene resin, limonene resin, dipentene resin, and β-pinene / limonene resin, which are made from the aforementioned terpene compounds, hydrogenated terpene resins that have undergone hydrogenation treatment can also be listed. As terpene phenols, resins copolymerized with the aforementioned terpene compounds and phenolic compounds, as well as resins that have undergone hydrogenation treatment, can be listed. Specifically, resins formed by condensing the aforementioned terpene compounds, phenolic compounds, and formaldehyde can be listed. It should be noted that phenolic compounds include, for example, phenol, bisphenol A, cresol, and xylenol. As aromatic modified terpene resins, resins obtained by modifying terpene resins with aromatic compounds, as well as resins that have undergone hydrogenation treatment, can be listed. It should be noted that, as aromatic compounds, there are no particular limitations as long as they have an aromatic ring. Examples include phenols such as phenol, alkylphenols, alkoxyphenols, and phenols containing unsaturated hydrocarbon groups; naphthols such as naphthols, alkylnaphthols, alkoxynaphthols, and naphthols containing unsaturated hydrocarbon groups; styrene derivatives such as styrene, alkylstyrene, alkoxystyrene, and styrene containing unsaturated hydrocarbon groups; coumarone, indene, etc.

[0204] "C5 resin" refers to resin obtained by polymerizing C5 fractions. Examples of C5 fractions include petroleum fractions with 4 to 5 carbon atoms, such as cyclopentadiene, pentene, pentadiene, and isoprene. Dicyclopentadiene resin (DCPD resin) is a suitable C5-based petroleum resin.

[0205] "C9 resin" refers to resins obtained by polymerizing C9 fractions, or products obtained by hydrogenation or modification of these fractions. Examples of C9 fractions include petroleum fractions with 8 to 10 carbon atoms, such as vinyltoluene, alkylstyrene, indene, and methylindene. Specific examples include coumarone-indene resin, coumarone resin, indene resin, and aromatic vinyl resins. For aromatic vinyl resins, based on economic efficiency, ease of processing, and good exothermic properties, homopolymers of α-methylstyrene (AMS resin) or styrene, or copolymers of α-methylstyrene and styrene, are preferred, with copolymers of α-methylstyrene and styrene being more preferred. Commercially available products from companies such as KRATON and Eastman Chemical can be used as aromatic vinyl resins.

[0206] "C5C9 resin" refers to a resin obtained by copolymerizing the aforementioned C5 fraction and C9 fraction, or it can be a product obtained by hydrogenation or modification of these fractions. Examples of C5 and C9 fractions include the aforementioned petroleum fractions. Commercially available products from companies such as Tosoh Corporation and Luhua Corporation can be used as C5C9 resin.

[0207] There are no particular limitations on the acrylic resin; for example, solvent-free acrylic resins can be used.

[0208] Solvent-free acrylic resins include (meth)acrylic resins (polymers) synthesized via high-temperature continuous polymerization (high-temperature continuous bulk polymerization) with minimal use of polymerization initiators, chain transfer agents, organic solvents, etc., as excipients (as described in US Patent 4,414,370, Japanese Patent Application Publication Nos. 59-6207, 5-58005, 1-313522, US Patent 5,010,166, and the Toa Synthetic Research Yearbook TREND2000 No. 3, pp. 42-45). It should be noted that in this invention, (meth)acrylic acid refers to both methacrylic acid and acrylic acid.

[0209] As monomeric components constituting the above-mentioned acrylic resins, examples include (meth)acrylic acid, (meth)acrylates (alkyl esters, aryl esters, aralkyl esters, etc.), (meth)acrylamide, and (meth)acrylamide derivatives, etc.

[0210] In addition, as a monomer component constituting the above-mentioned acrylic resin, aromatic vinyl groups such as styrene, α-methylstyrene, vinyltoluene, vinylnaphthalene, divinylbenzene, trivinylbenzene, and divinylnaphthalene can be used together with (meth)acrylic acid or (meth)acrylic acid derivatives.

[0211] The aforementioned acrylic resins can be resins composed solely of (meth)acrylic acid, or resins that incorporate components other than (meth)acrylic acid as constituent elements. Furthermore, the aforementioned acrylic resins may contain hydroxyl, carboxyl, or silanol groups, etc.

[0212] As a resin component, products from companies such as Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Co., Ltd., Rutgers Chemicals Co., Ltd., BASF Corporation, Arizona Chemical Co., Ltd., Nippon Paint Co., Ltd., Nippon Shokubai Co., Ltd., ENEOS Co., Ltd., Arakawa Chemical Industry Co., Ltd., Taoka Chemical Industry Co., Ltd., etc. can be used.

[0213] (III) Stearic acid

[0214] The rubber composition preferably contains stearic acid. The content of stearic acid, relative to 100 parts by weight of the rubber component, is, for example, greater than 0.5 parts by weight and less than 10.0 parts by weight. As stearic acid, conventionally known stearic acid can be used, for example, products from Nippon Yusen Co., Ltd., NOF Corporation, Kao Corporation, Fujifilm, Kojun Pharmaceutical Co., Ltd., Chiba Fatty Acid Co., Ltd., etc.

[0215] (IV) Anti-aging agents

[0216] The rubber composition preferably contains an antioxidant. The content of the antioxidant is, for example, greater than 0.5 parts by mass and less than 10 parts by mass, more preferably 1 part by mass or more, relative to 100 parts by mass of the rubber component.

[0217] As an anti-aging agent, there are no particular limitations. Examples include naphthylamine-based anti-aging agents such as phenyl-α-naphthylamine; diphenylamine-based anti-aging agents such as octyl diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; p-phenylenediamine-based anti-aging agents such as N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and N,N'-di-2-naphthyl-p-phenylenediamine; quinoline-based anti-aging agents such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol-based anti-aging agents such as 2,6-di-tert-butyl-4-methylphenol and styrylated phenol; and bisphenol-based, triphenol-based, and polyphenol-based anti-aging agents such as tetra-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane. Anti-aging agents can be used alone or in combination of two or more.

[0218] It should be noted that, as an anti-aging agent, products from companies such as Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinsei Chemical Co., Ltd., and Flexsys can be used.

[0219] (V) wax

[0220] The rubber composition preferably contains wax. The wax content is, for example, 0.5 to 20 parts by weight, preferably 1.0 to 15 parts by weight, and more preferably 1.5 to 10 parts by weight, relative to 100 parts by weight of the rubber component.

[0221] As for waxes, there are no particular limitations. Examples include petroleum-based waxes such as paraffin wax and microcrystalline wax; natural waxes such as plant-based waxes and animal-based waxes; and synthetic waxes made from polymers such as ethylene and propylene. They can be used alone or in combination of two or more.

[0222] It should be noted that products from companies such as Ouchi Shinshin Chemical Industry Co., Ltd., Nippon Seiwa Co., Ltd., and Seiko Chemical Co., Ltd. can be used as waxes.

[0223] (VI) Zinc oxide

[0224] The rubber composition may contain zinc oxide. The zinc oxide content, relative to 100 parts by weight of the rubber component, is, for example, greater than 0.5 parts by weight and less than 10 parts by weight. As the zinc oxide, conventionally known zinc oxides may be used, such as products from Mitsui Metal Mining Co., Ltd., Toho Zinc Industry Co., Ltd., Hakusui Technology Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., etc.

[0225] (VII) Crosslinking agents and vulcanization accelerators

[0226] The rubber composition preferably contains a crosslinking agent such as sulfur. The content of the crosslinking agent is, for example, greater than 0.1 parts by weight and less than 10.0 parts by weight per 100 parts by weight of the rubber component.

[0227] Examples of sulfur compounds commonly used in the rubber industry include powdered sulfur, settled sulfur, colloidal sulfur, insoluble sulfur, highly dispersed sulfur, and soluble sulfur. These can be used individually or in combination of two or more.

[0228] It should be noted that, for example, products from companies such as Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexsys Co., Ltd., Nippon Kanryu Kogyo Co., Ltd., and Hosoi Chemical Industry Co., Ltd. can be used as sulfur.

[0229] As crosslinking agents other than sulfur, specific examples include sulfur-containing vulcanizing agents such as Tackirol V200 manufactured by Taoka Chemical Industry Co., Ltd., KA9188 (1,6-bis(N,N'-dibenzylthiocarbamoyl dithio)hexane) manufactured by Lanxess, and organic peroxides such as dicumyl peroxide.

[0230] The rubber composition preferably contains a vulcanization accelerator. The content of the vulcanization accelerator relative to 100 parts by weight of the rubber component is, for example, greater than 0.3 parts by weight and less than 10.0 parts by weight.

[0231] Examples of vulcanization accelerators include thiazole-based accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazole disulfide, and N-cyclohexyl-2-benzothiazole sulfenamide; thiuram-based accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetra(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N-oxodiethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based accelerators such as diphenylguanidine, di-o-tolylguanidine, and o-tolylbiguanidine. These accelerators can be used alone or in combination of two or more.

[0232] (VIII) Other

[0233] In addition to the components mentioned above, the rubber composition may also contain additives commonly used in the tire industry, such as fatty acid metal salts, carboxylic acid metal salts, organic peroxides, and anti-reversion (vulcanization reversion) agents, as needed. The content of these additives relative to 100 parts by weight of the rubber component is, for example, greater than 0.1 parts by weight and less than 200 parts by weight.

[0234] (2) Preparation of rubber composition

[0235] The tread rubber composition can be manufactured by appropriately adjusting the various compounding materials mentioned above and by conventional methods, such as a basic mixing process that includes mixing the rubber components with fillers such as silica and carbon black, and a final mixing process that includes mixing the mixture obtained in the basic mixing process with a crosslinking agent.

[0236] Mixing can be carried out using well-known (closed) mixing machines such as Banbury internal mixers, kneaders, and open mills.

[0237] The mixing temperature in the basic mixing process is, for example, greater than 50°C and less than 200°C, and the mixing time is, for example, greater than 30 seconds and less than 30 minutes. In addition to the above-mentioned components, compounding agents used in the rubber industry in the past may be added as needed in the basic mixing process, such as softeners like oils, stearic acid, zinc oxide, antioxidants, waxes, vulcanization accelerators, etc.

[0238] In the final mixing process, the compound obtained in the basic mixing process is mixed with a crosslinking agent. The mixing temperature in the final mixing process is, for example, above room temperature and below 80°C, and the mixing time is, for example, above 1 minute and below 15 minutes. In addition to the above-mentioned components, vulcanization accelerators, zinc oxide, etc., may be added as needed during the final mixing process.

[0239] 2. Tire manufacturing

[0240] In this embodiment, the tire can be made by molding the rubber composition obtained above into a tread rubber of a specified shape, and then molding it together with other rubber parts on a tire forming machine using conventional methods, thereby producing an uncured tire.

[0241] Specifically, an uncured tire is produced by winding an inner liner (as a component to ensure tire air tightness), a carcass (as a component to withstand the load, impact, and air pressure borne by the tire), and a belt layer (as a component to strongly fasten the carcass and improve the rigidity of the tread) onto a forming drum. Bead portions (as components to fix the two ends of the carcass and secure the tire to the rim) are then arranged on both sides of the edge. After forming a ring shape, the tread is attached to the center of the outer periphery, and the sidewall is attached to the radially outer side to form the sidewall.

[0242] It should be noted that when the tread has a multi-layered structure consisting of a tread rubber layer and a base rubber layer, the aforementioned rubber composition is used as the rubber composition for forming the tread rubber layer. On the other hand, the rubber composition for forming the base rubber layer is essentially obtained by mixing the aforementioned rubber components and compounding materials, with appropriate variations in their proportions. Then, the tread rubber layer and the base rubber layer can be extruded together into a tread rubber of a specified shape and then, along with other tire components, formed on a tire forming machine using conventional methods, thereby producing an uncured tire.

[0243] The uncured tires are then heated and pressurized in a vulcanizing machine to obtain tires. The vulcanization process can be carried out using known vulcanization methods. For example, the vulcanization temperature is greater than 120°C and less than 200°C, and the vulcanization time is greater than 5 minutes and less than 15 minutes.

[0244] As described above, the resulting tire, due to the appropriate control of the ratio of the rubber composition for the tread and the relationship between the glass transition temperature of the rubber composition and the thickness of the tread, achieves a synergistic effect, thereby further improving the overall performance of the tire in terms of fuel consumption, wet grip, and wear resistance.

[0245] Secondly, the tires of the present invention are not particularly limited in category and can be used as tires for passenger cars, large passenger cars, large SUVs, trucks / buses, two-wheeled vehicles, racing tires, studless anti-skid tires (winter tires), all-season tires, run-flat tires, aircraft tires, mining tires, non-pneumatic tires, etc., and are preferably used as tires for passenger cars.

[0246]

Example

[0247] The following are examples (embodiments) that are considered preferred in practice, but the scope of the invention is not limited to these examples.

[0248] Tires consisting of treads and other rubber components formed from various compound materials as shown below were studied. The results of calculations based on the evaluation methods described below regarding fuel consumption performance, wet grip performance, abrasion resistance performance, and overall performance based on these individual properties are presented in the lower half of Tables 1-3.

[0249] 1. Manufacturing of rubber compositions for tire treads

[0250] Rubber compositions for tire treads are prepared using the various compounding materials shown below.

[0251] (1) Compounding materials

[0252] (a) Rubber composition

[0253] (I) NR: TSR-20

[0254] (II) SBR-1: Modified S-SBR manufactured based on Manufacturing Example 1 described below (styrene content: 20% by mass, vinyl content: 20% by mol), Tg: -60℃, Mw: 650,000.

[0255] (III) SBR-2: SLR 3402 manufactured by TRINSEO (styrene content: 15% by mass, vinyl content: 30% by mol), Tg: -62℃

[0256] (IV) SBR-3: HPR840 manufactured by ENEOS Materials (styrene content: 10% by mass, vinyl content: 42% by mol), Tg: -63℃

[0257] (V) SBR-4: Modified S-SBR (styrene content: 30 wt%, vinyl content: 22 mol%, Tg: -45°C, Mw: 1 million) produced by our company through manufacturing example 2 described later.

[0258] (VI) BR: Ube Industries, Inc.'s UBEPOL BR150B (high cis BR) (cis content 97% by mass, trans content 2% by mass, vinyl content 1% by mass)

[0259] (Manufacturing Example 1: Manufacturing of SBR-1)

[0260] The SBR-1 was prepared according to the following process: First, cyclohexane, tetrahydrofuran, styrene, and 1,3-butadiene were added to a nitrogen-purged autoclave reactor. After adjusting the temperature of the reactor contents, n-butyllithium was added to initiate polymerization. Polymerization was then carried out under adiabatic conditions. At the point where the polymerization conversion reached 99%, 1,3-butadiene was added, and polymerization continued for another 5 minutes. N,N-bis(trimethylsilyl)-3-aminopropyltrimethoxysilane was then added as a modifier to initiate the reaction. After the polymerization reaction was completed, 2,6-di-tert-butyl-p-cresol was added, and the solvent was removed by steam stripping. The mixture was then dried using hot rollers to obtain SBR-1.

[0261] (Manufacturing Example 2: Manufacturing of SBR-4)

[0262] The SBR-4 described above was prepared in the same manner as in Manufacturing Example 1, except that the target styrene content, vinyl content, and Tg were changed, and 3-dimethylaminopropyltriethoxysilane was used as a modifier.

[0263] (b) Compound materials other than rubber components

[0264] (I) Silica-1: ULTRASIL VN3 (N2SA: 175m) manufactured by Evonik Industries, Inc. 2 / g, average particle size: 17nm)

[0265] (II) Silica-2: ULTRASIL 9100Gr manufactured by Evonik Industries (N2SA: 235m) 2 / g, average particle size: 15nm)

[0266] (III) Silane coupling agent-1: Si266 (bis(3-triethoxysilylpropyl) disulfide) manufactured by Evonik Industries

[0267] (IV) Silane Coupling Agent-2: NXT (3-octanoylthiopropyltriethoxysilane) manufactured by Momentive.

[0268] (V) Carbon black: DIABLACK N220 manufactured by Mitsubishi Chemical Corporation (N2SA: 115m) 2 / g)

[0269] (VI) Resin composition-1: Syltraxx 4401 (α-methylstyrene resin) manufactured by Arizona Chemical Company

[0270] (VII) Resin Component-2: Oppera PR 383 (DCPD resin, softening point: 103℃) manufactured by ExxonMobil

[0271] (VIII) Oil: Vivatec 500 (aromatic processing oil: TDAE oil) manufactured by H&R Corporation

[0272] (IX) Zinc oxide: Zinc oxide No. 2 manufactured by Mitsui Metals & Minerals Co., Ltd.

[0273] (X) Anti-aging agent: Antigen 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Sumitomo Chemical Co., Ltd.

[0274] (XI) Stearic acid: Beaded stearic acid "Camellia" manufactured by Nippon Oil Company.

[0275] (XⅡ) Wax: OZOACE 0355 manufactured by Nippon Seiwa Co., Ltd.

[0276] (XⅢ) Sulfur: Powdered sulfur (containing 5% oil) manufactured by Tsurumi Chemical Industry Co., Ltd.

[0277] (XIV) Vulcanization accelerator: Nocceler CZ (N-cyclohexyl-2-benzothiazole sulfenamide (CBS)) manufactured by Ouchi Shinsei Chemical Co., Ltd.

[0278] (2) Preparation of rubber composition for tire tread

[0279] According to the formulas shown in Tables 1-3, the materials, except for sulfur and vulcanization accelerator, were mixed at 150°C for 5 minutes using a 1.7-liter Banbury internal mixer manufactured by Kobe Steel Co., Ltd. to obtain the mixture.

[0280] Then, sulfur and vulcanization accelerator are added to the mixture, and it is mixed for 5 minutes at 80°C using an open mill to obtain the rubber compositions for each tire tread.

[0281] 2. Manufacturing of pneumatic tires

[0282] (1) Tread Formation

[0283] Then, using the rubber composition obtained above, the tread is shaped into a specified shape.

[0284] Afterwards, it was bonded together with other tire components to form an uncured tire, and then vulcanized under pressure at 170°C for 10 minutes to manufacture the test tires of Examples 1 to 14 and Comparative Examples 1 to 7 shown in Tables 1 to 3 (tire size: 225 / 40R18, aspect ratio: 40%, tread thickness: 8mm, negative profile ratio: 35%).

[0285] Then, from the tread of each test tire, a viscoelasticity measurement sample measuring 20 mm long × 4 mm wide × 1 mm thick was taken with the tire circumference as the longer side. Using the GABO "EPLEXOR" series (registered trademark), the loss tangent at 30°C (30°C tanδ), the loss tangent at 0°C (0°C tanδ), and the complex modulus of elasticity at 0°C (0°C E) of the tread rubber composition were measured. * The glass transition temperature (Tg) is also shown. It should be noted that the thickness direction of the sample is the radial direction of the tire. Furthermore, the values ​​in the table are the average values ​​measured for each test tire.

[0286] Specifically, for tanδ at 30℃, the measurement was conducted in tensile deformation mode under the conditions of 30℃ temperature, 10Hz frequency, 5% initial strain, and 1% dynamic strain. Secondly, for tanδ at 0℃, the measurement was conducted in tensile deformation mode under the conditions of 0℃ temperature, 10Hz frequency, 5% initial strain, and 2.5% dynamic strain. Additionally, for E at 0℃... * The results were measured in elongation deformation mode under the conditions of 0℃ temperature, 10Hz frequency, 5% initial strain and 2.5% dynamic strain.

[0287] The glass transition temperature was determined based on the temperature distribution curve of the loss tangent (tanδ) measured using a viscoelasticity measuring device from the GABO EPLEXOR series. Specifically, the temperature distribution curve of tanδ was measured under conditions of a frequency of 10 Hz, initial strain of 10%, amplitude ±0.5%, and heating rate of 2 °C / min. The temperature with the largest tanδ value in the range above -60 °C and below 40 °C was taken as the glass transition temperature.

[0288] It should be noted that when there are two or more points with the largest tanδ value within the range of -60℃ to 40℃, the point with the lowest temperature is taken as the glass transition temperature. For example, if the peak value of tanδ is within the range of -60℃ to 40℃, according to the above definition, the peak temperature is taken as the glass transition temperature. Furthermore, for example, if the peak value of tanδ exists in the range below -60℃, and the temperature distribution curve shows that tanδ gradually decreases with increasing temperature within the range of -60℃ to 40℃, then according to the above definition, the glass transition temperature is -60℃.

[0289] 3. Parameters

[0290] Secondly, calculate Tg × tread thickness, SBR amount × aspect ratio, silica amount / negative profile ratio, resin content / negative profile ratio, and (0℃ tanδ / 0℃ E) * )×10 3 .

[0291] 4. Performance Evaluation

[0292] Performance evaluation focuses on fuel efficiency, wet grip, abrasion resistance, and the overall performance of these factors.

[0293] (1) Fuel consumption performance

[0294] Fuel consumption performance is evaluated based on the rolling resistance coefficient (RRC).

[0295] Specifically, using a rolling resistance testing machine, under the conditions of standard rim, standard internal pressure, and standard load, the rolling resistance coefficient of each test tire is measured when it travels on a drum at a speed of 80 km / h.

[0296] Then, the result of Comparative Example 1 is taken as 100 and exponentialized based on the following formula as an evaluation of fuel efficiency. The larger the value, the smaller the rolling resistance coefficient and the better the fuel efficiency (low fuel consumption).

[0297] Fuel efficiency = [(Results of Comparative Example 1) / (Results of the test tire)] × 100

[0298] (2) Wet grip performance

[0299] Each test tire was installed on all wheels of the vehicle and inflated with air to an internal pressure of 250 kPa. Then, the braking distance was measured while driving at 100 km / h on a wet test track.

[0300] Then, using the result of Comparative Example 1 as 100, the result is exponentialized based on the following formula to evaluate wet grip performance. A larger value indicates better wet grip performance.

[0301] Wet grip performance = [(Result of Comparative Example 1) / (Result of the test tire)] × 100

[0302] (3) Wear resistance

[0303] Each test tire was mounted on all wheels of the vehicle and inflated with air to an internal pressure of 250 kPa. The vehicle was then driven a specific distance along a test route. The tread depth was then measured, and the degree of reduction was determined. Next, the distance traveled corresponding to each 1 mm reduction in tread depth was calculated.

[0304] Then, using the result of Comparative Example 1 as 100, the result was exponentialized based on the following formula to evaluate the wear resistance performance. A larger value indicates a longer driving distance and better wear resistance performance.

[0305] Abrasion resistance = [(Results of the test tire) / (Results of Comparative Example 1)] × 100

[0306] (4) Comprehensive performance evaluation

[0307] The sum of the evaluation results in (1) to (3) is used as the evaluation of the overall performance.

[0308] Table 1

[0309]

[0310] Table 2

[0311]

[0312] Table 3

[0313]

[0314] The present invention has been described above based on embodiments, but the present invention is not limited to the embodiments described above. Various modifications can be made to the embodiments described above within the same or equivalent scope as the present invention.

[0315] This invention (1) is a tire,

[0316] It is a tire with a tread section, characterized in that,

[0317] The tread portion is formed using a rubber composition with a glass transition temperature (Tg) of -50°C to -15°C.

[0318] The rubber composition contains less than 25% by weight of styrene-butadiene rubber (SBR) in 100 parts by weight of the rubber component, and contains more than 90 parts by weight of silica and more than 55 parts by weight of resin component relative to 100 parts by weight of the rubber component.

[0319] The glass transition temperature Tg (°C) and the tread thickness G (mm) satisfy the following formula:

[0320] Tg×G<-150.

[0321] The present invention (2) is a tire according to the present invention (1), characterized in that the product of the glass transition temperature Tg (°C) and the thickness G (mm) of the tread (Tg×G) is less than -180.

[0322] The present invention (3) is a tire according to the present invention (2), characterized in that the product of the glass transition temperature Tg (°C) and the thickness G (mm) of the tread (Tg×G) is less than -200.

[0323] The present invention (4) is a tire of any combination of any one of the present invention (1) to (3), characterized in that the resin component is dicyclopentadiene resin or α-methylstyrene resin.

[0324] The present invention (5) is a tire of any combination of any one of the present invention (1) to (4), characterized in that the styrene content of the styrene-butadiene rubber (SBR) in the rubber component is less than 20% by mass.

[0325] The present invention (6) is a tire of any combination of any one of the present invention (1) to (5), characterized in that the glass transition temperature (Tg) of the rubber composition is above -40°C and below -20°C.

[0326] The present invention (7) is a tire of any combination of any one of the present invention (1) to (6), characterized in that the content of silica in the rubber composition is greater than 120 parts by mass relative to 100 parts by mass of rubber component.

[0327] The present invention (8) is a tire of any combination of any one of the present invention (1) to (7), characterized in that the particle size (average primary particle size) of the silica is less than 16 nm.

[0328] The present invention (9) is a tire of any combination of any one of the present invention (1) to (8), characterized in that the rubber composition contains a mercapto-based silane coupling agent.

[0329] The present invention (10) is a tire of any combination of any one of the present invention (1) to (9), characterized in that the thickness of the tread is more than 5 mm and less than 20 mm.

[0330] The present invention (11) is a tire of any combination of any one of the present inventions (1) to (10), characterized in that the product of the SBR content (parts by mass) in 100 parts by mass of the rubber component and the aspect ratio (%) of the tire is greater than 2000.

[0331] The present invention (12) is a tire of any combination of any one of the present inventions (1) to (11), characterized in that the ratio of the content (parts by mass) of the silica relative to 100 parts by mass of the rubber component to the negative profile ratio (%) of the tread surface is greater than 3.

[0332] The present invention (13) is a tire of any combination of any one of the present inventions (1) to (12), characterized in that the ratio of the content (parts by mass) of the resin component relative to 100 parts by mass of the rubber component to the negative profile ratio (%) of the tread surface is greater than 1.5.

[0333] The present invention (14) is a tire of any combination of any one of the present invention (1) to (13), characterized in that the loss tangent (30℃ tanδ) of the rubber composition measured in tensile deformation mode is 0.20 or more under the conditions of temperature 30℃, frequency 10Hz, initial strain 5% and dynamic strain 1%.

[0334] The present invention (15) is a tire of any combination of any of the present inventions (1) to (14), characterized in that the loss tangent (0°C tanδ) of the rubber composition, measured in tensile deformation mode under the conditions of 0°C, 10Hz frequency, 5% initial strain, and 2.5% dynamic strain, and the complex elastic modulus (0°C E) measured in elongation deformation mode under the conditions of 0°C, 10Hz frequency, 5% initial strain, and 2.5% dynamic strain, are... * ) satisfies the following formula,

[0335] [(0℃tanδ / 0℃E)] * )×10 3 >67.0.

Claims

1. A tire, comprising a tread portion, characterized in that, The tread portion is formed using a rubber composition with a glass transition temperature (Tg) of -50°C to -15°C. The rubber composition contains, in 100 parts by weight of rubber components, less than 25% by weight of styrene-butadiene rubber (SBR), and, relative to 100 parts by weight of rubber components, more than 90 parts by weight of silica and more than 55 parts by weight of resin components. The glass transition temperature Tg and the thickness G of the tread portion satisfy the following formula: Tg×G<-150, The glass transition temperature Tg is in °C, and the tread thickness G is in mm.

2. The tire according to claim 1, characterized in that, The product of the glass transition temperature Tg and the thickness G of the tread, Tg×G, is less than -180.

3. The tire according to claim 2, characterized in that, The product of the glass transition temperature Tg and the thickness G of the tread surface, Tg×G, is less than -200.

4. The tire according to any one of claims 1 to 3, characterized in that, The resin component is dicyclopentadiene resin or α-methylstyrene resin.

5. The tire according to any one of claims 1 to 3, characterized in that, The styrene content of the styrene-butadiene rubber (SBR) in the rubber composition is less than 20% by mass.

6. The tire according to any one of claims 1 to 3, characterized in that, The glass transition temperature (Tg) of the rubber composition is above -40°C and below -20°C.

7. The tire according to any one of claims 1 to 3, characterized in that, The content of silica in the rubber composition is greater than 120 parts by mass relative to 100 parts by mass of the rubber component.

8. The tire according to any one of claims 1 to 3, characterized in that, The silica has a particle size of less than 16 nm, and the particle size refers to the average primary particle size.

9. The tire according to any one of claims 1 to 3, characterized in that, The rubber composition contains a mercapto-based silane coupling agent.

10. The tire according to any one of claims 1 to 3, characterized in that, The thickness of the tread portion is 5mm or more and 20mm or less.

11. The tire according to any one of claims 1 to 3, characterized in that, The product of the SBR content in 100 parts by mass of the rubber component and the tire aspect ratio is greater than 2000. The unit for SBR quantity is parts by mass, and the unit for tire aspect ratio is ( ).

12. The tire according to any one of claims 1 to 3, characterized in that, The ratio of the silica content relative to 100 parts by mass of the rubber component to the negative profile ratio of the tread surface is greater than 3. The unit for the silica content is parts by mass, and the unit for the negative profile ratio is ( ).

13. The tire according to any one of claims 1 to 3, characterized in that, The ratio of the resin content relative to 100 parts by weight of the rubber component to the negative profile ratio of the tread surface is greater than 1.

5. The content of the resin component is expressed in parts by mass, and the negative profile ratio is expressed in parts by mass.

14. The tire according to any one of claims 1 to 3, characterized in that, The rubber composition, under conditions of 30°C, 10Hz, 5% initial strain, and 1% dynamic strain, has a loss tangent of 30°C (tanδ) greater than 0.20, as measured in tensile deformation mode.

15. The tire according to any one of claims 1 to 3, characterized in that, The loss tangent tanδ (0°C) of the rubber composition, measured in tensile deformation mode under conditions of 0°C, 10Hz, 5% initial strain, and 2.5% dynamic strain, is compared with the complex elastic modulus E (0°C) measured in elongation deformation mode under conditions of 0°C, 10Hz, 5% initial strain, and 2.5% dynamic strain. * Satisfy the following equation, [(0℃tanδ / 0℃E * 10 x 10 3 ]>67.0。 16. The tire according to any one of claims 1 to 3, characterized in that, The content of silica in the rubber composition is less than 190 parts by mass relative to 100 parts by mass of the rubber component.

17. The tire according to any one of claims 1 to 3, characterized in that, The content of the resin component is less than 75 parts by mass relative to 100 parts by mass of the rubber component.

18. The tire according to any one of claims 1 to 3, characterized in that, The styrene content of the styrene-butadiene rubber (SBR) in the rubber composition is 3% by mass or more.

Citation Information

Patent Citations

  • Bulk polymerization and polymer

    JP1984006207A

  • Catalytic lumpy production of cyclic ester modified acrylic polymer

    JP1989313522A

  • Bulk polymerization for manufacturing high solid content homogeneous copolymer

    JP1993058005B2

  • Small combustion furnace for manufacturing rice husk ash

    JP2009002594A

  • Rubber composition and tire

    JP2010111753A